Packed Red Blood Cells Are an Abundant and Proximate Potential Source of Nitric Oxide Synthase Inhibition - Zwemer, Charles F.; Davenport, Robertson D.; Gomez-Espina, Juan; Blanco-Gonzalez, Elisa; Whitesall, Steven E.; D'Alecy, Louis G. (PloS one, 2015)
We determined, for packed red blood cells (PRBC) and fresh frozen plasma, the maximum content, and ability to release the endogenous nitric oxide synthase (NOS) inhibitors asymmetric dimethylarginine (ADMA) and monomethylarginine (LNMMA). ADMA and LNMMA are near equipotent NOS inhibitors forming blood's total NOS inhibitory content. The balance between removal from, and addition to plasma determines their free concentrations. Removal from plasma is by well-characterized specific hydrolases while formation is restricted to posttranslational protein methylation. When released into plasma they can readily enter endothelial cells and inhibit NOS. Fresh rat and human whole blood contain substantial protein incorporated ADMA however; the maximum content of ADMA and LNMMA in PRBC and fresh frozen plasma has not been determined. We measured total (free and protein incorporated) ADMA and LNMMA content in PRBCs and fresh frozen plasma, as well as their incubation induced release, using HPLC with fluorescence detection. We tested the hypothesis that PRBC and fresh frozen plasma contain substantial inhibitory methylarginines that can be released chemically by complete in vitro acid hydrolysis or physiologically at 37°C by enzymatic blood proteolysis. In vitro strong-acid-hydrolysis revealed a large PRBC reservoir of ADMA (54.5 ± 9.7 µM) and LNMMA (58.9 ± 28.9 μM) that persisted over 42-d at 6° or -80°C. In vitro 5h incubation at 37°C nearly doubled free ADMA and LNMMNA concentration from PRBCs while no change was detected in fresh frozen plasma. The compelling physiological ramifications are that regardless of storage age, 1) PRBCs can rapidly release pathologically relevant quantities of ADMA and LNMMA when incubated and 2) PRBCs have a protein-incorporated inhibitory methylarginines reservoir 100 times that of normal free inhibitory methylarginines in blood and thus could represent a clinically relevant and proximate risk for iatrogenic NOS inhibition upon transfusion.